Evaluasi dan Perbaikan User Experience dari Aplikasi Perangkat Bergerak Unggul Sports Center Malang menggunakan Metode Heuristic Evaluation - Kresna Sudrajad; Herman Tolle; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Technological developments continue to grow every time. As time goes by, the development of the internet is increasing rapidly according to user needs. User experience has an important role in the development of a product or a system. User experience or someone who has a role in using products and systems. The value of the product or system can be known from the user experience how the user responds to using the product or system. This research was conducted to determine the feasibility, comfort level and user satisfaction of the product or system used can be known through user experience. To find out the quality level of the Superior Sport Center application in terms of user interface and user experience which has an impact on user satisfaction of the Superior Sport Center application. To determine the quality level of the Superior Sport Center application in terms of user interface and user experience, it can be done by testing Usability using the Heuristic Evaluation method. If the SUS score is above 68, it will considered to be above average and vice versa (Sauro, 2012). Of the 23 problems, there are 3 of the same problems, so the problems are summarized into 20 problems. The problems found consisted of 2 types, namely 16 problems regarding the interface and 4 problems regarding functionality. The severity rating category generated for each problem consists of 11 problems included in the catastrophic category, 8 problems included in the major category. The results of this study are: Usability research needs to be carried out using criteria that have not been used in this study. The use of other methods in researching other aspects of the Unggulsportcenter application to support progress in other aspects.